Immigration and citizenship. The logic of allocating rights in social action - Peláez-Paz, Carlos; Sanz Abad, Jesús (Cuadernos de Trabajo Social, 2018)
We explain the contributions of anthropological thinking regarding the relationship among the forms of inclusion of immigrant populations in Spain, the recognition of economic, social and cultural rights, and citizenship. We are witnessing the transformation from Marshall’s classic idea of “social citizenship”, based on the universality of rights, to a vision of segmented access to rights in a global neoliberal context, in which citizenship becomes a mechanism for exclusion rather than inclusion.We describe the production of the otherness of the impoverished and dangerous migrant, which gives rise to their differential inclusion. The legal system and institutional management play a key role in this classification process, being accorded legitimacy through discourses of scarcity and security. We reflect on the function of social work in this regard and the tension between social control-oriented models and others based on a transformative approach involving the promotion of social equality and justice.